2022
DOI: 10.21608/aasj.2022.272406
|View full text |Cite
|
Sign up to set email alerts
|

Land capability and suitability assessment of some soils El-Galaba plain, Aswan, Egypt

Abstract: The objective of this work aims to study the land capability and suitability under drip and sprinkler irrigation systems of some soils located in El-Galaba plain, west of Edfu city, Aswan governorate, Egypt. The soil texture of the study area was mainly sand, loamy sand and sandy loam with different percentages of gravel content; they are deep soil profiles. Organic matter (OM) content is low and decrease with depth. ECe values vary widely from 0.3 -26.7 dS/m indicting that the studied soils are non-saline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Results for land suitability according to the ASLE program showed that the study area's soils were highly suitable (S1), suitable (S2), moderately suitable (S3), marginally suitable (S4), and currently and permanently unsuitable (N1 and N2, respectively) for 28 field and vegetable crops and fruits. Mohamed Rashed and et al, (2022) discovered that the suitability of the land for growing the following crops-sugar beet, cotton, wheat, tomato, soy bean, maize, onion, pepper, cabbage, olive, date palm, alfalfa, grape, and fig-was highly suitable (S1), suitable (S2), moderately suitable (S3), marginally suitable (S4), and currently unsuitable-N1. The applied system of land evaluation (ASLE) for arid and semi-arid settings was used to evaluate the suitability of particular crops in these locations.…”
Section: Introductionmentioning
confidence: 99%
“…Results for land suitability according to the ASLE program showed that the study area's soils were highly suitable (S1), suitable (S2), moderately suitable (S3), marginally suitable (S4), and currently and permanently unsuitable (N1 and N2, respectively) for 28 field and vegetable crops and fruits. Mohamed Rashed and et al, (2022) discovered that the suitability of the land for growing the following crops-sugar beet, cotton, wheat, tomato, soy bean, maize, onion, pepper, cabbage, olive, date palm, alfalfa, grape, and fig-was highly suitable (S1), suitable (S2), moderately suitable (S3), marginally suitable (S4), and currently unsuitable-N1. The applied system of land evaluation (ASLE) for arid and semi-arid settings was used to evaluate the suitability of particular crops in these locations.…”
Section: Introductionmentioning
confidence: 99%